Fluorocyclisation via I(I)/I(III) catalysis: a concise route to fluorinated oxazolines - Scheidt, Felix; Thiehoff, Christian; Yilmaz, Gülay; Meyer, Stephanie; Daniliuc, Constantin G.; Kehr, Gerald; Gilmour, Ryan (Beilstein Journal of Organic Chemistry, 2018)
Herein, we describe a catalytic fluorooxygenation of readily accessible N-allylcarboxamides via an I(I)/I(III) manifold to generate 2-oxazolines containing a fluoromethyl group. Catalysis is conditional on the oxidation competence of Selectfluor®, whilst HF serves as both a fluoride source and Brønsted acid activator. The C(sp3)–F bond of the mono-fluoromethyl unit and the C(sp3)–O bond of the ring are aligned in a synclinal relationship thereby engaging in stabilising hyperconjugative interactions with vicinal, electron-rich σ-bonds (σC–C→σ*C–F and σC–H→σ*C–O). This manifestation of the stereoelectronic gauche effect was established by X-ray crystallographic analysis of a representative example. Given the importance of fluorine in drug discovery, its ability to modulate conformation, and the prevalence of the 2-oxazoline scaffold in Nature, this strategy provides a rapid entry into an important bioisostere class.
Keywords: catalysis; cyclisation; fluorination; gauche effect; hypervalent iodine; oxazolines